BASED LEARNING MANAGEMENT IDEAS TO IMPROVE THE CREATIVITY OF THINKING - Zulfakar, Zulfakar (EARR (Educational Administration Research and Review), 2017)
Student are less actively involved event tend to be passive in the classroom of learning process in process of frequent lecturer dominant, students spent more time waiting for a grain of lecturers rather than seek and find their own knowledge, skills and attitudes they need, if the learning conditions that own amximize the role and involvement lecturers as well as minimizing the role and involvement of students it occurs in higher education that resulted learning becomes monotonous. Rigidity is learning to give birth mindset learners who do not thrive, is limited, and even hamper the creativity of student thinking. This study aims to develop ideas based learning management in improving, the creativity of thinking, by applying the four main pillars, namely: 1) learn to know something, 2) learn to understand something, 3) learn to actualize something, and 4) studying the creation of something. The method used in tis research is the method of research and development is commonly abbreviated (R D). As for knowing improvement of student learning outcomes using the formula Pm = P2-P1. This research instrument synergy between faculty and students in implementing the four main pillars of ideas based learning management indicators: a) mastery and getted of the material, b) understanding and deepening of the material, c) actualize material, d) the creation of matter.   The results showed a significant increase applied before and after the learning management based on the idea of three classes the first semester of the 2014/2015 academic year student of management education FIP Teachers' Training College Mataram taken at random, while the sample in this study amounted to 150 students with details as follow : 50 students of the third semester, 50 students and 50 students of the fifth semester VII semester. With an average increase of 6.42 %, with details as follows: third semester, an increase of 6.5 %, the fifth semester increased by 6.74% while the seventh semester an increase of 6.02%.